2016
DOI: 10.12659/msm.897832
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine-Like Receptor 1 Regulates the Proliferation and Migration of Vascular Smooth Muscle Cells

Abstract: BackgroundWe aimed to explore how chemokine-like receptor 1 (CMKLR1) influences the proliferation and migration of vascular smooth muscle cells (VSMCs).Material/MethodsNormal VSMCs, negative control VSMCs interfered by CMKLR1 gene, and VSMCs with stable knockdown of CMKLR1 gene were divided into the control group, PDGF group, negative-shRNA group, and CMKLR1-shRNA group. Both cell number counting and BrdU incorporation assays were employed to investigate the proliferation status of VSMCs. Transwell migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…investigation revealed that knockdown of chemerin receptor, CMKRL1, inhibited proliferation and migration of vascular SMCs (Liu et al, 2016), suggesting main chemerin-induced activity through CMKLR1. These apparent discrepant results may result from variable cell proliferation protocol and SMC origin, but also to lower concentrations of chemerin compared to those used in previously cited studies.…”
Section: Discussionmentioning
confidence: 99%
“…investigation revealed that knockdown of chemerin receptor, CMKRL1, inhibited proliferation and migration of vascular SMCs (Liu et al, 2016), suggesting main chemerin-induced activity through CMKLR1. These apparent discrepant results may result from variable cell proliferation protocol and SMC origin, but also to lower concentrations of chemerin compared to those used in previously cited studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the isolated rat thoracic aorta, CMKLR1 agonist chemerin-9 caused arterial contraction in a dose-dependent manner, while CMKLR1 antagonist CCX832 inhibited phenylephrine-induced vasoconstriction [37]. Our previous study indicated that the proliferation and migration of VSMCs induced by platelet-derived growth factor (PDGF) was inhibited by knockdown of CMKLR1 [18]. Our current data suggested that chemerin stimulated the progression of atherosclerosis by promoting p38 MAPK phosphorylation and NF- κ Bp65 expression.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study, we found that circulating chemerin levels increased after carotid balloon injury, and knockdown of chemerin significantly inhibited the VSMCs proliferation in vitro as well as prohibited carotid neointimal hyperplasia in vivo after angioplasty [17]. Further investigation revealed that knockdown of chemerin receptor, chemokine-like receptor 1 (CMKLR1), inhibited the proliferation and migration of VSMCs [18].…”
Section: Introductionmentioning
confidence: 99%
“…In an adoptive transfer study of the model, they found that wild type bone marrow reconstitution into ChemR23 -/mice, augmented the inflammatory response [178]. As stated in the Introduction 4.1.1, there are large amount of nonleukocyte cell types which do express the chemerin receptors, including adipocytes, vascular smooth muscle cells, endothelial and lung epithelial cells [263,266,218,176]. 123…”
Section: Non-leukocyte Cellsmentioning
confidence: 96%
“…vascular smooth muscle cells [124,266]. Finally, ChemR23 receptor influences the proliferation and migration of vascular smooth muscle cells [124,266].…”
Section: Chemokine-like Receptor 1 (Chemr23)mentioning
confidence: 99%